India's structural transformation and role in the world economy - Codrina Rada; Rüdiger von Arnim (The University of Utah, Department of Economics, 2012)
This paper employs (1) a three-sector structuralist model of development with informal and formal activities and (2) a global one-sector model with demand determined outputs and bargained distribution to investigate whether India's growth performance can be sustained, where the country might face constraints to growth, and how India's growth matters in the global economy.
Keywords: O11; O17; O53; F01; 330; structural change; informal sector; India; global demand